Tidal Current Influence on Distributing Submarine Groundwater Discharge (SGD) Area in the North Lombok Waters, Indonesia [Pengaruh Arus Pasang Surut dalam Distribusi Keluaran Air Tanah Lepas Pantai (KALP) di Perairan Lombok Utara, Indonesia] - Ulung Jantama Wisha; Gunardi Kusumah (Faculty of Fisheries and Marine Universitas Airlangga, 2019)
AbstractSubmarine Groundwater Discharge (SGD) has been found in the North Lombok Island. This phenomenon is strongly related to the watershed from Rinjani Mountain permeated in the form of underwater seepages. The largest seepage was observed in Krakas Beach. The emergence of these seepages may affect water quality and nutrient pollution in the surrounding by which the distribution is mainly induced by the tidal current regime. This study aimed to determine the influence of tidal current on low-temperature groundwater distribution and to analyze the environmental issues resulted from this phenomenon. Flow model and statistical analysis were employed to determine the transport pattern of SGD. The tidal current moved southwestward during the high tidal condition ranging from 0-0.15 cm/s. While tidal current flowed northeastward during the low tidal condition ranging from 0-0.3 cm/s. The temperature fluctuation follows the changes of surface elevation around SGD in which the correlation value between those two parameters reached 63 percent. This proves that the cold-water transportation depends on the fluctuation of tidal current (tidal pumping), resulting in the imbalanced ecosystem, especially during the high tidal condition when a greater water mass transport takes place.AbstrakKeluaran Air Tanah Lepas Pantai (KALP) telah ditemukan di utara Pulau Lombok. Fenomena ini sangat dipengaruhi oleh daerah aliran air Gunung Rinjani yang meresap dalam bentuk rembesan bawah air. Rembesan terbesar diketahui berada di Pantai Krakas. Kemunculan rembesan ini mungkin berdampak pada kualitas perairan dan polusi nutrien di sekitarnya yang mana distribusinya sangat dipicu oleh pengaruh arus pasang surut. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh dari arus pasang surut terhadap distribusi air dingin dan menganalisis masalah lingkungan akibat dari kondisi tersebut. Arus pasang surut bergerak menuju barat daya saat kondisi pasang berkisar antara 0-0,15 cm/s, sedangkan arus pasang surut bergerak menuju timur laut pada kondisi surut berkisar antara 0-0,32 cm/s. Fluktuasi suhu mengikuti perubahan elevasi muka air di lokasi KALP dimana nilai korelasi dari kedua parameter tersebut mencapai 63 persen. Hal ini membuktikan bahwa transpor air dingin bergantung pada fluktuasi arus pasang surut, menyebabkan ketidakseimbangan ekosistem, khususnya pada kondisi pasang ketika mekanisme transpor masa air yang lebih besar sedang berlangsung.